The problem of utilization of felling leaves of cities and wastes of animal-farming farm and ways of its solutions - Sonko S. P.; Pushkarova - Bezdil T. M.; Sukhanova I. P.; Vasilenko O. V.; Gursky I. M; Bezdil R. V. (Людина і довкілля: Проблеми неоекології, 2017)
Puporse. Analysis of the environmental problems associated with disposal of wastes of different origin and justification for their use vermykultury solving, evaluation of air (ammonia and hydrogen sulfide) in the area of livestock complex, аssessment of the suitability of fallen leaves of a hazel tree as a filler for a vermicompost. Methods. Field - air sampling versatile portable gas analyzer UG-2 type, Laboratory methods - determination of the content of carbohydrates, proteins in the fallen leaves. Results. Analyzes some environmental problems: burning city leaves and dry grass and environmentally environment near enterprises with livestock production. The condition of the air in the area of livestock complex - rabbit farm of "Krolikoff" posted on the site Mankivskoho in Cherkasy region over the years 2012-2014 at distances of 10, 20, 50, 100, 200 meters from the handling of manure and 300 meters - at the border of the nearest existing residential development. The highest content of ammonia in the air found in the area of handling manure 9.2 mg / m3 (in winter) and 18.2 mg / m3 (in summer), significantly higher than the permissible sanitary-epidemiological norms. With increasing distance from the storage area decreases the concentration of ammonia and hydrogen sulfide in the air, at a distance of 20 m - 2.1 (in summer) and 2.2 times (winter), 100 m (at the border of sanitary zones for objects of this class of danger) - 26 and 23 times. Fugitive emissions do not create a rabbit farm on the edge of existing residential buildings abnormal levels of air pollution. Conclusions. A necessary condition is the creation of environmental and covering manure storage on all sides with a layer of peat or ground; continue to use manure as organic fertilizer to improve quality and accelerate chemical processes of fermentation technology used vermykomposting.